Psychological diagnostics of risky behavior of adolescents - Rakhimkulova, Anastasiia (Psychiatry, Neurology and Medical Psychology, 2018)
The article reflects practical results of the research on adolescent risky behaviorand specifically – the psychodiagnostics stage. Traditionally therapeutic impact on riskyadolescents is not quite effective. We assume that the main reason of poor efficiency of thepsychological correction of risky behavior lies in the inability to address precise factors that standout for particular adolescent since these factors may vary substantially. In our research we were ableto distinguish three factors and their wide array of components that affect adolescent’s engagementinto such types of behavior. Grounding on those we elaborated a detailed procedure for runningpsychological diagnostics that enables to identify and to further impact actual psychological targetsduring further coming psychological correction classes. The psychodiagnostics procedure aims atanalyzing the following phenomena: adolescent’s predisposition to self-harming and suicidalbehavior; current pshyco-emotional state; attitude to self and its components; stress-resilience; typicalcoping strategies and psychological adaptation. The proposed system of methods also enablesto identify every adolescent’s strengths that a psychotherapist can employ as the basis for newskills’ development.